Perancangan Media Pembelajaran Multimedia Interaktif Peninggalan Sejarah Indonesia Menggunakan Metode Web Based Learning (Study Kasus : SDS Cerdas Bangsa Namorambe) - Sinuhaji, Suanti Perwita Br; Allwine, Allwine; Wijaya, Vera; Mardiah, Mardiah (Universitas Islam Negeri Sumatera Utara, 2023)
Education is one area that has a strong influence on internet technology, especially in teaching and learning activities. Technological development is inseparable from the utilization of Human Resources (HR) in supporting learning and being a solution in a lack of learning media on Indonesian historical heritage material in the SDS Cerdas Bangsa Namorambe Case study, especially in class IV SD students. Therefore the authors conducted research on interactive multimedia learning media. This learning media was made due to the lack of learning media so that the lack of design in learning made students less interested in the teaching and learning process so that it was made using web based learning methods. Web Based Learning (WBL) is a technology-based learning system that is used as the utilization of web technology in learning by delivering access to material through web pages. In developing the system used system analysis use case diagrams and activity diagrams with the type of research using the Research and Development (R & D) method. Keywords:Learning Media, Interactive Multimedia, Web Based Learning.